EBV status has prognostic implication among young patients with angioimmunoblastic T‐cell lymphoma. (2nd December 2019) - Eladl, Ahmed E.; Shimada, Kazuyuki; Suzuki, Yuka; Takahara, Taishi; Kato, Seiichi; Kohno, Kei; Elsayed, Ahmed Ali; Wu, Chun‐Chieh; Tokunaga, Takashi; Kinoshita, Tomohiro; Sakata‐Yanagimoto, Mamiko; Nakamura, Shigeo; et al.
Abstract: Epstein‐Barr virus (EBV)‐positive B cells have been detected in 66%‐86% of patients with angioimmunoblastic T‐cell lymphoma (AITL). However, it remains controversial whether EBV status has an impact on the survival of patients with AITL. In this study, we aimed to reevaluate the impact of EBV on the clinicopathological characteristics of AITL. In particular, we focused on the impact of EBV in younger patients with AITL. In total, 270 cases of AITL were studied. Epstein‐Barr virus‐positive B cells were detected in 191 (71%) cases (EBER + group). Among the patients who received anthracycline‐based therapy, the EBER status did not affect the overall survival (OS) or progression‐free survival (PFS). In the younger group of AITL (≤60 years), PFS was significantly worse in the EBER − group compared to the EBER + group ( P = .0013). Furthermore, the multivariate analysis identified EBER‐negative status, thrombocytopenia, and elevated serum IgA level as significant adverse prognostic factors for PFS ( P < .001, P < .001, and P = .002). Based on these findings, we constructed new prognostic model for the younger group, based on three adverse factors. We classified the patients into two risk groups: low risk (no or 1 adverse factor) and high risk (2 or 3 adverse factors). This new model for younger patients with AITL showed that both OS and PFS were significantly related to the level of risk ( P < .0001). In summary, this study showed that, among younger patients with AITL, an EBER + status significantly improved prognosis compared to an EBER − status. Our new prognostic model should be applicable to younger patients with AITL. Abstract : In the younger group of AITL, PFS was significantly worse in the EBER − group compared to the EBER + group ( P = .0013). Furthermore, the multivariate analysis identified EBER‐negative status, thrombocytopenia, and elevated serum IgA level as significant adverse prognostic factors for PFS ( P < .001, P < .001, and P = .002).